Molecular architecture and microporous structure of low mature lacustrine kerogen: A multi-parameter modeling of the Triassic Yanchang Formation, Ordos Basin - Yinhai Song; Meijun Li; Xiaoqiang Liu; Xia Luo; Qingyong Luo; Qingbin Xie; Haochen Chen; Zhihao Wang (Fuel, 2027)

Study on three-dimensional multiphysics-coupled load-following operation of small lead-cooled fast reactors for grid peak shaving - Haochen Huang; Daogang Lu; Yu Liu; Yuchao Wang; Hao Ding; Danting Sui (Annals of Nuclear Energy, 2026)

Generative imaging sonar forward depth estimation for underwater dense scene reconstruction - Zhengyan Zhang; Yanze Lu; Haochen Hu; Bing Wang; Jinghua Lin; Chih-yung Wen (Ocean Engineering, 2026)

Mitophagy-replenishment strategy targeting the aberrant endogenous dsDNA to enhance bone healing quality in the elderly - Zhengxia Ni; Yiyang Huang; Kun Xi; Jiannan Mao; Lingjun Wang; Jincheng Tang; Wenbo Wang; Xinzhao Jiang; Haochen Jiang; Liang Zhou; Jie Wu; Zhouye Ding; et al. (Chemical Engineering Journal, 2026)

Association Between Circulating Essential Metals and Pregnancy Loss: A Systematic Review and Meta-Analysis - Liqin Wen; Meiqi Ren; Liantong Wang; Jinhua Cheng; Haoqing Liang; Haochen Ai; Yuxin Yao; Shuying Lin; Zhekai Cui; Xiao Shi (Journal of Trace Elements in Medicine and Biology, 2026)

A bounding surface model for methane hydrate-bearing sediment incorporating hydrate dissociation - Lujun Wang; Dongyu Yang; Haoqi Song; Haochen Yang; Linfang Xu; Bo Ning; Bin Zhu (Computers and Geotechnics, 2026)

Dabie mountain topography and cross-regional transport regulating nitrate heterogeneity during a severe haze episode in Jiangxi - Haochen Zuo; Mingxuan Xu; Yangfan Jin; Kangjia Gong; Xiang Tu; Yao Wang; Xiaodong Xie; Jiao Wang; Jianlin Hu (Atmospheric Environment, 2026)

Retraction notice to “Mobilization of contaminants: Potential for soil remediation and unintended consequences” [Sci. Total Environ. 839 (2022) 156373] - Manish Kumar; Nanthi Bolan; Tahereh Jasemizad; Lokesh P. Padhye; Srinidhi Sridharan; Lal Singh; Shiv Bolan; James O'Connor; Haochen Zhao; Sabry M. Shaheen; Hocheol Song; Kadambot H.M. Siddique; et al. (Science of The Total Environment, 2026)

Retraction notice to “Boron contamination and its risk management in terrestrial and aquatic environmental settings” [Sci. Total Environ. 894 (2023) 164744] - Shiv Bolan; Hasintha Wijesekara; Dhulmy Amarasiri; Tao Zhang; Péter Ragályi; Milka Brdar-Jokanović; Márk Rékási; Jui-Yen Lin; Lokesh P. Padhye; Haochen Zhao; Liuwei Wang; Jörg Rinklebe; et al. (Science of The Total Environment, 2026)

Hydrogen radical is also a critical reductive defluorination species in the Far-UVC-activated sulfite process - Xiangyang Hou; Shu Xu; Qiuling Lu; Kai Wang; Haonan Lu; Haochen Zhang; Yuying Li; Minchao Liu; Jin Jiang; Shuo Li; Jun Ma; Tiangang Luan; et al. (Journal of Hazardous Materials, 2026)

Solar light irradiation activated dichloramine for efficient abatement of micropollutants - Peng Su; Wenjun Zhang; Haochen Zhang; Haonan Lu; Qiuling Lu; Kai Wang; Yuying Li; Xiaolong Xu; Changyu Liu; Jun Ma; Tao Yang (Water Research, 2026)

CeO2/La2O2CO3 heterostructures as high-performance adsorbents: Interfacial synergy and regeneration for fluoride removal - Xin Xiao; Huimin Zhang; Zhiling Qiu; Zhangjian Qian; Haochen Ding; Litong Zhang; Xiangmei Wang (Process Safety and Environmental Protection, 2026)

Recovery of silver and silicon from spent solar cells by direct separation driven by galvanic and chemical etching in molten chloride - Haochen Wang; Hongya Wang; Shiyu Wang; Yubo Zhou; Danfeng Wang; Fengyin Zhou; Xinyi Li; Junmin Peng; Xiang Chen; Dihua Wang; Huayi Yin (Science Bulletin, 2026)

A recyclable and self-supporting spinel anode for electrochemical activation of peroxymonosulfate to sulfamethoxazole degradation - Wentao Qiu; Hao Shi; Mengyi Tang; Xiaodan Zhang; Haochen Wang; Wei Li; Dihua Wang (Journal of Environmental Chemical Engineering, 2026)

Ultrasound-activated azido-sulfonamide prodrug nanoparticle with antibacterial peptide targeting for selective bacterial infection therapy - Jiali Sun; Jiahui Pan; Xitong Ren; Zecheng Chang; Wenfang Wang; Guoqing Wang; Jianting Xu; Jianshi Du; Haochen Yao (Chemical Engineering Journal, 2026)

Insight into poplar fractionation enhancement via an eco-manufacturing process using sulfonated magnetic polystyrene solid acid and biphasic solvent - Haochen Du; Cuiyi Liang; Shijun Liu; Xuesong Tan; Yang Chen; Shiyou Xing; Yu Zhang; Wei Liu; Wen Wang; Xin Shi; Zhongming Wang; Wei Qi (Chemical Engineering Journal, 2026)

A review of tree nut allergens and their processing for decreasing allergenicity - Haochen Ye; Tanying Zhang; Siyu Ren; Jingwei Jiang; Zeyu Peng; Jia Cao; Jinshen Chu; Bowen Li; Haozhe Yi; Binjia Zhang; Huan Wang; Xiaowen Pi (Trends in Food Science & Technology, 2026)

Dairy flavor measurements from materials to human perception: Emerging trends and applications - Yangfan Guo; Ying Wang; Haochen Zhou; Xinying Xu; Dongxiao Sun-Waterhouse; Shan Ding; Fanyu Meng; Tao Jiang; Bei Wang (Trends in Food Science & Technology, 2026)

Characterization of Interlayer Resistivity Responses in Crack-Containing Rock-Like Materials and Analysis of Failure Precursors - Tingye Qi; Hongtao Xu; Guorui Feng; Tian Qiu; Haochen Wang; Linfei Wang; Siyuan Cheng; Xinkai Qi; Lubin Li (Rock Mechanics and Rock Engineering, 2026)

Suppressing electronic leakage in GDC-based electrolytes: A multi-layered architecture approach for enhanced performance and stability in intermediate-temperature SOFCs - Haochen Dang; Yuanjie Zhang; Laizhen Song; Enhua Wang (Fuel, 2026)

High-temperature corrosion mechanism of ferritic stainless steel in steam-hydrogen atmosphere for solid oxide electrolysis cell based on reactive force field method - Enhua Wang; Yajing Zhang; Jingwen Mao; Haochen Dang; Minggao Ouyang; Haoran Hu; Hewu Wang; Yadi Liu; Youpeng Chen; Languang Lu; Dongsheng Ren (Fuel, 2026)

From behavior to taste: Developmental trajectories of anxiety-like phenotypes unveil a neuroendocrine link to flesh quality in economic crustaceans - Hengtong Liu; Sisi Sheng; Yiming Li; Wanting Huang; Wenbin Liu; Haochen Wang; Cheng Chi; Dingdong Zhang (Food Bioscience, 2026)

CitrusNet: A vision transformer-CNN approach for citrus detection from multi-source imagery with multi-scale feature integration - Haochen Wang; Juan Shi; Hamed Karimian; Fei Wang; Faizan Javed; Bo Liu; Shengnan Shi; Ziwei Li; Yang Tao (Computers and Electronics in Agriculture, 2026)

A green approach for the selective recovery of Copper, Lead, and Tin from End-of-Life photovoltaic solder ribbons - Shun Dai; Shiyu Wang; Haochen Wang; Fengyin Zhou; Simin Xu; Yongxin Wu; Muya Cai; Xinyi Li; Shuaibo Gao; Wei Li; Bowen Deng; Dihua Wang; et al. (Waste Management, 2026)

Chebyshev-based dynamic analysis of pre-stressed composite stepped stiffened combined shells - Haochen Hu; Kunpeng Zhu; Rui Zhong; Qingshan Wang; Zhou Huang (Ocean Engineering, 2026)

A comparative study on the occurrence and pore structure characteristics of CH4 and CO2 hydrates in sandy sediments using SEM-EDS technology - Lujun Wang; Haochen Yang; Chuanqi Sun; Jianye Sun; Xiluo Hao; Chengfeng Li; Bin Zhu; Yunmin Chen (Gas Science and Engineering, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

SUMOylation in Mitochondrial Quality Control: Mechanisms and Implications for Neurodegenerative Disease - Qingya Wu; Dengying Fan; Jianhui Ren; Yafang Xing; Zhengzheng Chen; Haochen Jin; Yisheng Lu; Xiaopeng Wang; Hua Zheng (Molecular Neurobiology, 2026)

Nanoplastic-mediated disruption of freshwater carbon cycling via modulating of plankton communities - Peng Wang; Haochen Yang; Chengjing Li; Zihao Fu; Qianqian Xiang; Xia Luo; Liqiang Chen (Journal of Hazardous Materials, 2025)

Pore-scale simulation of oil-water flow in shale media after fracture hits: an integrated approach using U-net and lattice Boltzmann method - Peiyu Li; Yilei Song; Jiatong Jiang; Zhaojie Song; Xiao Han; Xiukun Wang; Haochen Ren; Jixiang He (Fuel, 2025)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

New insight into acidic fluoride removal by tannic acid-mediated cerium oxides: Performance and mechanism - Haochen Wang; Menghan Huang; Zhe Xu; Hui Qiu (Chemical Engineering Journal, 2025)

DFT-enhanced machine learning for accurate PLQY prediction and inverse design of novel MR-TADF materials - Haochen Shi; Yiming Shi; Guangjun Zeng; Haichang Wang; Yumei Hu; Bo Qiao; Zhiqin Liang; Suling Zhao; Man-Chung Tang; Dandan Song (Chemical Engineering Journal, 2025)

Optimizing Water Allocation and Industry Structure: A Multi-Scenario Comparison by Using Interval Fuzzy Multi-Level Programming Model - Chunxiao Ma; Ruxin Bai; Shifu Wang; Zhiqiang Yan; Haochen Shi (Water Resources Management, 2025)

Enhancing the Feature Representation of Protein Sequence Descriptors in Protein-Protein Interaction Prediction - Hoai-Nhan Tran; Nguyen-Phuc-Xuan Quynh; Haochen Zhao; Jianxin Wang (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Exploring the recreational micromobility in relation to historic urban areas and social media: Insights from machine learning approaches - Hao Huang; Haochen Shi; Xinjian Li; Yankai Wang (Landscape and Urban Planning, 2025)

Quantitative effects of potassium application on potato tuber yield, quality, and potassium uptake in China: A meta-analysis - Fan Zhang; Xiukang Wang; Hao He; Haochen Wang; Bolun Zhang; Shiju Liu; Ruixue Chen; Yaru Zhang; Yandong Wang; Hao Ren; Yu Wang; Juan Han (Field Crops Research, 2025)

The “lost” aqueous supercritical fluids recorded in highly refractory mantle peridotites - Haochen Duan; Yunpeng Dong; Huimin Yu; Wenyu Wang; Fang Huang (Earth and Planetary Science Letters, 2025)

MobileYOLO-Cyano: An enhanced deep learning approach for precise classification of cyanobacterial genera in water quality monitoring - Yang Tao; Hamed Karimian; Juan Shi; Haochen Wang; Xuchu Yang; Yanchang Xu; Yi Yang (Water Research, 2025)

Enhanced degradation of tetracycline over the novel biochar doped with Cu-Mn by peroxymonosulfate activation: Performance evaluation and mechanisms - Xinyu Li; Haochen Li; Xiaofei Zong; Yanbo Wang; Jiahui Wu; Yuwei Deng; Yuxuan Ye; Wentao Li; Qiang Li; Fei Pan (Journal of Environmental Chemical Engineering, 2025)

Construction of efficient proton channels with silica-encapsulated carbon nanotubes for proton exchange membrane water electrolysers - Min Huang; Yang Li; Haochen Lu; Siyi Gao; Felix Kwofie; Xinyao Guo; Quentin Meyer; Yi Wang; Chuan Zhao; Nanwen Li; Yi Cheng (Chemical Engineering Journal, 2025)

Mitigating overestimation in lithium-ion battery recycling LCA: The critical role of ex-post data and operational parameters - Shiyu Wang; Fengyin Zhou; Jingjing Zhao; Hongya Wang; Xin qu; Muya Cai; Haochen Wang; Xu Wang; Dihua Wang; Huayi Yin (Chemical Engineering Journal, 2025)

Impact of biochar on the fate of 15N-labelled fertilizer in water-saving and flooding irrigated rice-soil system under three different nitrogen sources - Xi Chen; Zhihui Wang; Ningbo Cui; Li Guo; Kangning Yu; Haochen Jin; Shikuan Sun (Plant and Soil, 2025)

Seismic response and failure evolution of an irregular slope containing bedding planes and high-position surficial soil layer - Qianqian Feng; Yunsheng Wang; Jianxian He; Xiaolong Hu; Haochen Wu; Dongyu Hu; Shicheng Liu; Tao Tang (Landslides, 2025)

Compounding effects of Lake and urbanization on summer precipitation in the Greater Chicago area - Jiali Wang; Zhao Yang; Theron Moustakes; Haochen Tan; Rao Kotamarthi; Alberto Martili; Robert Jackson; Paytsar Muradyan; Scott Collis; Joseph O'Brien; Dev Niyogi; Ashish Sharma (Urban Climate, 2025)

High-touch surfaces with moderate contamination levels as key nodes in microbial dissemination - Pengcheng Zhao; Peihua Wang; Tzehau Lam; Nan Zhang; Huanhuan Wang; Haochen Zhang; Jiquan Liu; Yuguo Li (Journal of Hazardous Materials, 2025)

Bimetallic Mn and Cr co-doped nickel cobalt phosphide nanoneedle arrays as bifunctional electro catalysts for overall water splitting - Yongyi Zhang; Mingyan Zhang; Haochen Zhang; Dan Han; Jinping Wang; Rui Yang; Chunling Zuo; Xiaoshuang Chen (Fuel, 2025)

Cigarette smoke-induced PPAR signaling dysregulation accelerates Alzheimer's disease pathogenesis and cognitive decline in 5xFAD mice - Yunqi Xie; Haochen Wang; Yajie Zhang; Bingbing Lin; Yuting Chen; Kai Li; Huanwen Tang; Qian Sun (Food and Chemical Toxicology, 2025)

Fomite transmission of MRSA in hospital dental departments: A modelling study based on real healthcare worker-patient contact patterns - Nan Zhang; Haochen Zhang; Mengting Wang; Shenglan Xiao (Building and Environment, 2025)

Identification of carbon and nitrogen multimedia fate in bioretention based on 13C and 15N isotope tracers - Jianlong Wang; Haochen Qin; Xueting Wang; Fangfang Lv; Yimeng Dai (Environmental Research, 2025)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

Rational design of paclitaxel prodrugs for facile preparation of in-situ therapeutic system in antitumor applications - Lanqing Wang; Zhaofan Yang; Guanyu Jin; Bingzheng Yu; Wei Zhang; Xuesi Chen; Haochen Yao; Cuiping Yao; Shixian Lv (Chemical Engineering Journal, 2025)

Silver nanoparticles alter plankton-mediated carbon cycle processes in freshwater mesocosms - Peng Wang; Qianqian Xiang; Zihao Fu; Chengjing Li; Haochen Yang; Jun Zhang; Xia Luo; Liqiang Chen (Journal of Hazardous Materials, 2025)

Crystalline carbon nitride derived self-assembly composite membranes with enhanced self-cleaning performance toward dye/salt separation - Yujing Qiu; Haochen Xu; Ying Zhou; Beizhao Chen; Zhongying Wang; Yi Yang; Qile Fang; Ying Mei (Journal of Environmental Management, 2025)

A novel domain knowledge augmented large language model based medical conversation system for sustainable smart city development - Haochen Zou; Yongli Wang; Anqi Huang (Sustainable Cities and Society, 2025)

Ocean mixed layer depth 2000–2020: Estimation assessment and long-term trends - Haochen Tang; Chen Wang; Huimin Li; Yijun He (Progress in Oceanography, 2025)

Mechanism of enhanced oil recovery via carbon dioxide flooding in kerogen nanopores: A molecular dynamics approach - Yiqun Zhang; Yiquan Jiang; Jing Zhang; Haochen Huang; Tianyu Wang; Jinshan Wang; Yingqiao Ren; Xu Cui (Fuel, 2025)

Shaddock peels biochar doping with Fe-Co bimetal for peroxymonosulfate activation on the degradation of tetracycline: The influence of HCO3− and PO43− - Haochen Li; Jiahui Wu; Ao Ren; Yao Qu; Xiaofei Zong; Yaoyao Gong; Dandan Wang; Yuxuan Ye; Qiang Li; Zhenbin Wu; Fei Pan (Environmental Research, 2025)

Delineating and refining the equity of revealed accessibility of express service amenities: A case study of Guangzhou - Yankai Wang; Quanyu Liu; Tao Mei; Haochen Shi; Miaoxi Zhao; Binbin Sun (Applied Geography, 2025)

Light-enhanced ion transport and fouling resistance properties of metal/semiconductor heterojunction nanochannel membranes for osmotic energy recovery in real-world conditions - Haochen Lu; Jin Wang; Derong Zhang; Tongxin Liao; Shangzhen Li; Lei Lei; Zhiyan Liu; Bingjie Du; Xudong Wang; Lei Wang (Water Research, 2025)

Exploring recreational walking and its correlated built environment factors in river corridor space through a trajectory sematic-based approach - Haochen Shi; Liyue Zhang; Ding Ma; Menghan Zhang; Mo Wang; Zongcai Wei (Urban Forestry & Urban Greening, 2025)

Hydrogel-based materials for microbial/enzyme immobilization: Advanced applications in wastewater treatment - Haochen Hu; Wenxin Lu; Shipeng Li; Xingkun Zhou; Chengyuan Zhu; Xingang Wang; Hongliang Dai; Hongya Geng (Chemical Engineering Journal, 2025)

Bioinspired tailless FWMAV design for agricultural plant protection in greenhouses - Yongwei Yan; Fa Song; Wenzhe Wang; Haochen Zhu; Jiyu Sun (Computers and Electronics in Agriculture, 2025)

Enhancing protonic ceramic fuel cell performance with catalyst-loaded dendritic porous anode for biomass ethanol internal reforming - Haochen Dang; Enhua Wang (Chemical Engineering Journal, 2025)

Chitosan-based immunomodulatory bioadhesive hydrogel promotes liver hemostasis and repair - Wenxin Wang; Haochen Yao; Jie Xia; Xinjian Wan; Jinglei Wu (Carbohydrate Polymers, 2025)

The outer-inner loop mechanism of alkali carbonate-modified BaFe2O4 during the biomass char chemical looping partial oxidation and hydrogen generation (CLPH) process - Haochen Sun; Hengyang Miao; Zhiqing Wang; Zheyu Liu; Chao He; Yitian Fang (Chemical Engineering Journal, 2025)

Enhanced defluoridation of neutral and weakly alkaline water using well-dispersed cerium-based metal–organic framework mediated by tannic acid - Liting Wang; Haochen Wang; Hui Qiu (Chemical Engineering Journal, 2025)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Serum trace elements and osteoarthritis: A meta-analysis and Mendelian randomization study - Haoyan Shi; Haochen Wang; Minghao Yu; Jianbang Su; Ze Zhao; Tianqi Gao; Qian Zhang; Yingliang Wei (Journal of Trace Elements in Medicine and Biology, 2024)

A disposable microfluidic aptasensor for one-step and real-time detection of sub-femtomolar-level aflatoxin B1 in food - Haochen Qi; Jian Zhang; Xueyong Zhang; Li Lv; Tianqi Wang; Erhui Huang; Jayne Wu; Lei Zheng (Food Research International, 2024)

Preparation of polyethylene based composite nanofiltration membrane and its application in removal of heavy metals for water purification - Lin Wang; Guiru Zhu; Haochen Ge; Yunbo Tong; Lingling Li; Ziqi Wang; Congjie Gao (Desalination, 2024)

Machine Learning-Driven Precise Design of Stable OLED Materials: Predicting and Enhancing Multi-State C-N Bond Dissociation Energies - Yiming Shi; Haochen Shi; Haichang Wang; Chun-Jung Chen; Yaoyao Li; Bo Qiao; Zhiqin Liang; Suling Zhao; Deyu Hang; Zheng Xu; Dandan Song (Chemical Engineering Journal, 2024)

Insight into adsorption behaviors of shale oil in kerogen slit by molecular dynamics - Yiqun Zhang; Yiquan Jiang; Qiang Wei; Haochen Huang; Tianyu Wang; Hao Xiong; Jinshan Wang; Yingqiao Ren; Xu Cui (Fuel, 2024)

Dietary flavonoids: Role in preventing neurodegenerative diseases caused by brain aging by modulating the gut microbiota - Siyu Liu; Haochen Dai; Rui Wang; Xin Zhang (Food Bioscience, 2024)

In-situ repair of failed LiFePO4 cathode using residual Li- and C-containing impurities from active material separation process - Ben Wang; Yanwei Yin; Haoyuan Deng; Guangming Li; Haochen Zhu; Wenzhi He (Chemical Engineering Journal, 2024)

Burning behavior of hydrogen jet flame inhibited by a wire mesh screen - Zhenhua Tang; Zhirong Wang; Hui Xu; Yuhan Xiao; Haochen Lu; Kun Zhao (Process Safety and Environmental Protection, 2024)

Relying on free radical degradation of cephalexin by novel Cu1Co2@C catalyzed by permonosulfate: Mechanism and degradation pathways - Xiaofei Zong; Xinyu Li; Jiahui Wu; Xi Ni; Haochen Li; Zhengyu Han; Rongling Wang; Yuwei Deng; Yuxuan Ye; Lei Sun; Qiang Li; Fei Pan (Journal of Water Process Engineering, 2024)

Heat-moisture treatment of freshly harvested high-amylose maize kernels improves its starch thermal stability and enzymatic resistance - Zhonghua Gu; Gaomin Cheng; Xianying Sha; Haochen Wu; Xinwei Wang; Renyong Zhao; Qiang Huang; Yinong Feng; Jihua Tang; Hongxin Jiang (Carbohydrate Polymers, 2024)

From trajectories to network: Delineating the spatial pattern of recreational walking in Guangzhou - Haochen Shi; Linlin Yao; Qiqi Liu; Yankai Wang; Zongcai Wei; Miaoxi Zhao; Ding Ma (Applied Geography, 2024)

Machine learning-enabled discovery of multi-resonance TADF molecules: Unraveling PLQY predictions from molecular structures - Haochen Shi; Yiming Shi; Zhiqin Liang; Suling Zhao; Bo Qiao; Zheng Xu; Lijuan Wang; Dandan Song (Chemical Engineering Journal, 2024)

Three-stage behaviors of K2CO3 catalyst during CO2 catalytic gasification of coal - Haochen Sun; Zhiqing Wang; Hengyang Miao; Yangang Mei; Jiejie Huang; Jin Bai; Yitian Fang (Fuel, 2024)

Carbon slow-release and enhanced nitrogen removal performance of plant residue-based composite filler and ecological mechanisms in constructed wetland application - Zhaoyang Li; Tianyin Huang; Wei Wu; Xiaoyi Xu; Bingdang Wu; Jinlong Zhuang; Jingjing Yang; Haochen Shi; Yang Zhang; Bin Wang (Bioresource Technology, 2024)

Studies on regional ozone formation sensitivities and transport with higher spatiotemporal resolutions in a stereoscopic dimension: GEMS and vertical observations - Haochen Peng; Chengzhi Xing; Yikai Li; Chengxin Zhang; Jinan Lin; Jingkai Xue; Xiaohan Wang; Yuhang Song; Xinhan Niu; Cheng Liu (Atmospheric Research, 2024)

Exploring the ecological meanings of temperature sensitivity of ecosystem respiration from different methods - Yang Zhang; Gaofeng Zhu; Kun Zhang; Heng Huang; Liyang He; Cong Xu; Huiling Chen; Yonghong Su; Yuzhong Zhang; Haochen Fan; Boyuan Wang (Science of The Total Environment, 2024)

Energy partitioning over an irrigated vineyard in arid northwest China: Variation characteristics, influence degree, and path of influencing factors - Huiling Chen; Yongtai Zhu; Gaofeng Zhu; Yang Zhang; Liyang He; Cong Xu; Kun Zhang; Jing Wang; Ramamoorthy Ayyamperumal; Haochen Fan; Boyuan Wang (Agricultural and Forest Meteorology, 2024)

Effects of distinct lipid phases and packaging on alleviating the quality deterioration of surimi gels during frozen storage - Yuxin Wang; Xidong Jiao; Nana Zhang; Bowen Yan; Haochen Ding; Weijian Ye; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Food Bioscience, 2024)

The fabrication of thin-film nanocomposite membrane for organic solvent forward osmosis via host-guest chemistry of α-cyclodextrin - Lin Wang; Fangkun Xiao; Haochen Ge; Yunbo Tong; Congjie Gao; Guiru Zhu (Desalination, 2024)

Engineering mesoporous nascent MnO2 colloids for efficient elimination of emerging organic contaminants - Zhuoyue Liu; Dong Cheng; Haochen Yin; Jianghao Zhao; Jiale Zhang; Rongzhi Chen; Shengjiong Yang; Jing Wei; Gen Wang (Journal of Water Process Engineering, 2024)

Thawing of goose meat by simultaneous dual frequency ultrasound for process efficiency: Thawing rate, quality attributes, structural characteristics - Wangbin Shi; Yang Wang; Xingyu Chen; Haochen Hu; Xi Chen; Benjamin Kumah Mintah; Mokhtar Dabbour; Xiangren Meng; Zhaoli Zhang; Ronghai He; Haile Ma (Innovative Food Science & Emerging Technologies, 2024)

A new ternary diagram to decipher the evolution of maturity and biodegradation of crude oil using ESI FT-ICR MS - Dongyong Wang; Meijun Li; Jianfa Chen; Haochen Chen; Quan Shi (Fuel, 2024)

The biological source and paleoenvironment implication of rare short-chain lanostanes in alkaline lacustrine sediments - Dongyong Wang; Meijun Li; Jianfa Chen; Hong Xiao; Xianli Zou; Lu Yang; Haochen Chen; Huiqiang Qin (Organic Geochemistry, 2023)

Life cycle environmental benefits of recycling waste liquor and chemicals in production of lignocellulosic bioethanol - Yunzi Hu; Haochen Du; Luyao Xu; Cuiyi Liang; Yu Zhang; Zhigang Sun; Carol Sze Ki Lin; Wen Wang; Wei Qi (Bioresource Technology, 2023)

Mitogenome analysis reveals predominantly ancient Yellow River origin of population inhabiting Datong agro-pastoral ecotone along Great Wall - Yuqing Yan; Panxin Du; Jihong Zhang; Ruilan Li; Haoquan Bao; Qingli Fang; Ye Gao; Hailiang Meng; Yiran Xu; Haochen Shi; Hailong Yan; Xin Chang; et al. (Molecular Genetics and Genomics, 2023)

Research on Black Smoke Detection and Class Evaluation Method for Ships Based on YOLOv5s-CMBI Multi-Feature Fusion - Shipeng Wang; Yang Han; Mengmeng Yu; Haiyan Wang; Zhen Wang; Guangzheng Li; Haochen Yu (Journal of Marine Science and Engineering, 2023)
To enhance the real-time detection accuracy of ship exhaust plumes and further quantify the degree of darkness, this study proposes a multi-feature fusion approach that combines the YOLOv5s-CMBI algorithm for ship exhaust plume detection with the Ringerman Blackness-based grading method. Firstly, diverse datasets are integrated and a subset of the data is subjected to standard optical model aerosolization to form a dataset for ship exhaust plume detection. Subsequently, building upon the YOLOv5s architecture, the CBAM convolutional attention mechanism is incorporated to augment the network’s focus on ship exhaust plume regions while suppressing irrelevant information. Simultaneously, inspired by the BiFPN structure with weighted bidirectional feature pyramids, a lightweight network named Tiny-BiFPN is devised to enable multi-path feature fusion. The Adaptive Spatial Feature Fusion (ASFF) mechanism is introduced to counteract the impact of feature scale disparities. The EIoU_Loss is employed as the localization loss function to enhance both regression accuracy and convergence speed of the model. Lastly, leveraging the k-means clustering algorithm, color information is mined through histogram analysis to determine clustering centers. The Mahalanobis distance is used to compute sample similarity, and the Ringerman Blackness-based method is employed to categorize darkness levels. Ship exhaust plume grades are estimated by computing a weighted average grayscale ratio between the effective exhaust plume region and the background region. Experimental results reveal that the proposed algorithm achieves improvements of approximately 3.8% in detection accuracy, 5.7% in recall rate, and 4.6% in mean average precision (mAP0.5) compared to the original model. The accuracy of ship exhaust plume darkness grading attains 92.1%. The methodology presented in this study holds significant implications for the establishment and application of future ship exhaust plume monitoring mechanisms.

RETRACTED: Boron contamination and its risk management in terrestrial and aquatic environmental settings - Shiv Bolan; Hasintha Wijesekara; Dhulmy Amarasiri; Tao Zhang; Péter Ragályi; Milka Brdar-Jokanović; Márk Rékási; Jui-Yen Lin; Lokesh P. Padhye; Haochen Zhao; Liuwei Wang; Jörg Rinklebe; et al. (Science of The Total Environment, 2023)

An epoxide-based covalent sensor to detect cardiac proteome aggregation in a cardio-oncology model - Hao Jin; Di Shen; Biao Jing; Zhenduo Zhang; Zhiming Wang; Rui Sun; Huaiyue Zhang; Jialu Sun; Haochen Lyu; Yu Liu; Lili Wang (Analytica Chimica Acta, 2023)

Nitrilotriacetic acid-assisted Mn(II) activated periodate for rapid and long-lasting degradation of carbamazepine: The importance of Mn(IV)-oxo species - Yishi Wang; Wei Qiu; Xiaohui Lu; Xiaoqun Zhou; Haochen Zhang; Xiuxue Gong; Baocai Gong; Jun Ma (Water Research, 2023)

Effects of gestational ambient extreme temperature exposures on the risk of preterm birth in China: A sibling-matched study based on a multi-center prospective cohort - Qiong Wang; Lina Yin; Haochen Wu; Zhoupeng Ren; Simin He; Aiqun Huang; Cunrui Huang (Science of The Total Environment, 2023)

Remediation of sulfonamides-contaminated groundwater through in-situ activation of peroxymonosulfate by supported hierarchical CuO/MgO nanosheets - Zhuoyue Liu; Lei Ge; Ke Wang; Haochen Yin; Danyang Li; Shengjiong Yang; Gen Wang; Delu Miao (Journal of Water Process Engineering, 2023)

A novel economic benefit calculation modeling applying to coal mining - Zhicheng Zhang; Qi Ding; Guorui Feng; Tingye Qi; Yanyu Guo; Yiwen Wang; Haochen Wang; Xinyu Gao (Environment, Development and Sustainability, 2023)

Simulation study of novel methods for water reinjection efficiency improvement of a doublet system in guantao sandstone geothermal reservoir - Chao Yu; Yiqun Zhang; Yawen Tan; Xianzhi Song; Gaosheng Wang; Haochen Huang; Bo Zhang (Geothermics, 2023)

Periodate activation with stable MgMn2O4 spinel for bisphenol A removal: Radical and non-radical pathways - Jiaxin Yu; Wei Qiu; Xinchen Lin; Yishi Wang; Xiaohui Lu; Yongbo Yu; Haiteng Gu; Song Heng; Haochen Zhang; Jun Ma (Chemical Engineering Journal, 2023)

Impact of different roofing mitigation strategies on near-surface temperature and energy consumption over the Chicago metropolitan area during a heatwave event - Haochen Tan; Rao Kotamarthi; Jiali Wang; Yun Qian; T.C. Chakraborty (Science of The Total Environment, 2023)

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)

Green credit policy and the liquidity risks of heavily polluting enterprises - Tuo Wang; Xiaoxing Liu; Haochen Guo (Environmental Science and Pollution Research, 2022)

Response of microscopical hyperspectral data to past climatic variable - Lingjun Wang; Teng Fei; Meng Bian; Yadan Xu; Haochen Zhang; Yonghong Zheng; Haifeng Zhu (Theoretical and Applied Climatology, 2022)

Dietary preferences and potential ecological impact on the zooplankton community of Nemopilema nomurai based on stable isotope and fatty acid analyses - Junjian Wang; Chaolun Li; Guang Yang; Zhencheng Tao; Yanqing Wang; Haochen Xian (Journal of Oceanology and Limnology, 2022)

Numerical investigations on load transfer of mooring line considering chain–seabed dynamic interaction - Shengjie Rui; Zhen Guo; Lizhong Wang; Haochen Liu; Wenjie Zhou (Marine Georesources & Geotechnology, 2021)

Omega-3 fatty acid protects cardiomyocytes against hypoxia-induced injury through targeting MiR-210-3p/CASP8AP2 axis - Xueju Yu; Fengyao Liu; Yuting Liu; Bingqing Bai; Han Yin; Haochen Wang; Yingqing Feng; Huan Ma; Qingshan Geng (Molecular and Cellular Biochemistry, 2021)

Machine Learning-based Weather Support for the 2022 Winter Olympics - Jiangjiang Xia; Haochen Li; Yanyan Kang; Chen Yu; Lei Ji; Lve Wu; Xiao Lou; Guangxiang Zhu; Zaiwen Wang; Zhongwei Yan; Lizhi Wang; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2020)

A Model Output Machine Learning Method for Grid Temperature Forecasts in the Beijing Area - Haochen Li; Chen Yu; Jiangjiang Xia; Yingchun Wang; Jiang Zhu; Pingwen Zhang (Advances in Atmospheric Sciences, 2019)